Charasteristics of COVID-19 Patients Treated At Santa Elisabeth Medan Hospital 2020 - Nency Triputri; Noni Novisari Soeroso (Talenta Publisher, 2021)
Corona Virus Disease (COVID-19) is a disease caused by a new type of coronavirus (SARS-CoV-2). This virus was first discovered in Wuhan, China for the first time and has infected 90,308 people as of March 2, 2020. Infection is transmitted by large droplets or droplets within 1 - 2 m, which are generated during coughing and sneezing by symptomatic patients and people without symptoms. This infection is acquired by inhaling these droplets or touching a contaminated surface and then touching the nose, mouth and eyes. To see the characteristics of COVID-19 patients who are treated at the Santa Elisabeth Hospital Medan in 2020. Type of research is a descriptive study with a cross-sectional study design with a retrospective approach using total sampling technique. This type of research data is secondary data obtained from the medical record data of positive COVID-19 patients confirmed to be hospitalized in several Medan city hospitals in 2020.Of the 230 study samples, 147 confirmed positive COVID-19 patients were found, dominated by the age range 46-55 years. The sex most common is male. The most common clinical symptoms are respiratory disorders such as coughing, shortness of breath and fever.The number of confirmed positive patients at the hospital. Santa Elisabeth in March to October 2020 is 147 people (51.1%).